Detection and Isolation of Rickettsia tillamookensis (Rickettsiales: Rickettsiaceae) From Ixodes pacificus (Acari: Ixodidae) From Multiple Regions of California. Issue 4 (25th April 2022) - Paddock, Christopher D; Slater, Kimetha; Swei, Andrea; Zambrano, Maria L; Kleinjan, Joyce E; Padgett, Kerry A; Saunders, Megan E M; Andrews, Elizabeth S; Trent, Erin; Zhong, Jianmin; Sambado, Samantha; Goldsmith, Cynthia S; et al.
Abstract: The western black-legged tick ( Ixodes pacificus ) is the most frequently identified human-biting tick species in the western United States and the principal vector of at least three recognized bacterial pathogens of humans. A potentially pathogenic Rickettsia species, first described in 1978 and recently characterized as a novel transitional group agent designated as Rickettsia tillamookensi s, also exists among populations of I. pacificus, although the distribution and frequency of this agent are poorly known. We evaluated DNA extracts from 348 host-seeking I. pacificus nymphs collected from 9 locations in five California counties, and from 916 I. pacificus adults collected from 24 locations in 13 counties, by using a real-time PCR designed specifically to detect DNA of R. tillamookensis. DNA of R. tillamookensis was detected in 10 (2.9%) nymphs (95% CI: 1.6–5.2%) and 17 (1.9%) adults (95% CI: 1.2–3.0%) from 11 counties of northern California. Although site-specific infection rates varied greatly, frequencies of infection remained consistently low when aggregated by stage, sex, habitat type, or geographical region. Four novel isolates of R. tillamookensis were cultivated in Vero E6 cells from individual adult ticks collected from Alameda, Nevada, and Yolo counties. Four historical isolates, serotyped previously as 'Tillamook-like' strains over 40 yr ago, were revived from long-term storage in liquid nitrogen and confirmed subsequently by molecular methods as isolates of R. tillamookensis . The potential public health impact of R. tillamookensis requires further investigation.